Partial deletion of long arm of chromosome 11[del(11)(q23)]: Jacobsen syndrome. Two new cases and review of the clinical findings. - Schinzel, A (1977)
Two cases, a boy and a girl, with the 11q-(Jacobsen) syndrome are reported. Findings common to both and typical for this chromosome aberration include a narrow protruding forehead, hypertelorism, non-horizontal position of the eyes, ptosis, strabismus, broad root, and short upturned tip of thenose, carp mouth, receding chin, misshapen ears, simian creases, and severe mental retardation. In addition, one patient had pyloric stenosis and an inguinal hernia. Growth retardation and microcephaly were not found in either of them. The karyotypes revealed de novo-deletions of the long arm of one chromosome 11,del(11)(q23).